Contribución a la apropiación de la educación ambiental a través de la tradición oral y la comprensión lectora (2020)
The present work carried out an intervention with a didactic sequence to improve in an articulated way in a group of secondary school students their knowledge in Environmental Education and reading comprehension, entitled "Contribution to the appropriation of environmental education through oral tradition and reading comprehension "in the Dagua Educational Institution, in the municipality of Dagua, Valle del Cauca. The objective was that at the same time there was little motivation to read and almost null reading habits of the students, awareness would be opened environmental and that young people would opt for more sustainable and environmentally friendly lifestyles A qualitative methodology of descriptive cutting was developed in three stages, one of sensitization and diagnosis, another of application of the didactic sequence and an end where it is evaluated. Demonstrate that it is possible to work together in the understanding of texts and educational environments Environmental with strategies designed for that purpose, since in comparison between the first diagnostic exercise and the evaluation exercise, students significantly improved their reading skills and their environmental awareness.